PERBEDAAN BENTUK DAN UKURAN RUGAE PALATINA ANTARA MAMAK DAN KAMANAKAN LAKI-LAKI SUKU MINANGKABAU DI WILAYAH LUHAK NAN TIGO - Ovy Prima Damara; Nila Kasuma; Eni Rahmi (Andalas Dental Journal, 2017)
Forensic odontology in dentistry is used to identify victims. Several methods can be used, such as rugoscopy. Rugoscopy is a victim identification method by evaluating the palatal rugae. Rugoscopy is very advantageous due to its low cost, fast results and practical nature. Palatal rugae is protected from trauma and high temperature due to its internal position in the oral cavity. Palatal rugae is an individualistic structure, though it bears several resemblance with the hereditary pattern due to the polygenic mechanism. The purpose of this research is to determine the difference of palatal rugae shape and size between uncle and nephew in Minangkabau ethnics. This study is an analytical observational study with a cross sectional approach. A total of 78 pairs of uncle and nephew of the Minangkabau ethnicity in Luhak Nan Tigo. Palatal rugae is classified using the Thomaz and Khutze classification. Data were analyzed by using Mann Whitney non-parametric statistical analysis. Data analysis show the palatal rugae shape of uncle and nephew from the Minangkabau ethnicity is dominated by a wavy shape, followed by curvy, straight, unified and circular shapes. The palatal rugae size of uncle and naphew from the Minangkabau ethnicity is dominated by primary size, followed by secondary and fragmenter size. Mann Whitney analysis revealed no significant difference of palatal rugae shape and size between uncle and nephew in Minangkabau ethnics (p>0,05), though there is a significant difference in the unified shape (p<0,05). Palatal rugae shape and size have a similar pattern with hereditery patterns, though not identical. Palatal rugae may be used as a secondary method of victim identification Keywords : Rugoscopy, palatal rugae, uncle and nephew